Floating charge debenture as an Islamic collateral instrument / Nurusshazani Atiqah Shahrul Anuar - Shahrul Anuar, Nurusshazani Atiqah (2019)
The floating charges played a major part in the provision of debt financing to enterprises for over a century has been well documented. Within the same timeframe, there is a several statutory crystallization of the charge which raised doubts as to the financial capability to rely on the charge in order to expand and secure loans. A debenture typically describes a set of events where the payment crystallizes into a defined charge when there are certain occurrences and the borrower is able to enforce the charge. A prominently stipulated crystallization is when an asset subject to floating charge seeks to create a charge or some form of security. The value expressed to the borrower under a debenture is somewhat close to that of a beneficiary under a trust fund without crystallization. As long as the trust fund is properly managed, the beneficiary does not have a right to any specific asset under the trust until the trust is terminated or a crystallisation event in the case of a debenture. However, there are a few doubts of Shariah regulation on floating charge in Islamic banking transaction. If the Islamic banking to be found included the non-shariah compliant charge, the transaction might be trade of usury which is prohibited in Islam. This study is qualitative by using descriptive analysis. Therefore, the focus of this study is to identify the Shariah status of floating charge debenture and differentiate it with Ar-Rahnu contract. Apart from that, some an established Shariah principle will be appraised with a special focus to make sure whether the floating charge permissible and benefits to Muslim economic or not. On top of that, it is believed that floating charge debenture can be applied in Islamic transaction due to its crystallization.